Comparative Study of Islamic Banking Between Malaysia and Pakistan - Kurrum Faisal, Jamal (2006)
This study deals with several objectives and 7 aspects namely promotion, product, preference, knowledge, performance, problem and infrastructure in making comparison on Islamic banking between Pakistan and Malaysia. Two techniques were used to answer the research objectives. Firstly, the qualitative method (questionnaire) and second the quantitative method (analysis of financial statements of the leading banks). The findings of thesis indicate that there are few differences and similarities exist between Malaysia and Pakistan in Islamic banking practices. The lack of awareness of Islamic banking is very high in Pakistan as compared to Malaysia. A few promotions were used by Islamic banks in Pakistan while in Malaysia customers are knowledgeable about Islamic banking because banks promote them aggressively. However there should be continuous and strong support by each government to stimulate Islamic banking system. The study finds that respondents in both countries agree that Islamic banking is a very important part of banking system primarily for religious factor in case of Pakistan and as for Malaysia it serves as an alternative banking system that appeals to both Muslims and non-Muslims. The study provides evidence that there is a vast potential of future growth in Islamic banking in both countries.